Penguatan Jiwa Kewirausahaan Melalui Pelatihan dan Pemasaran Kerajinan Tangan di Lingkungan Dayah - Ismail; Abdul Aziz (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2024)
The entrepreneurial mindset development program through handicraft training and marketing in Islamic boarding schools (dayah) is a strategic effort to equip students (santri) with productive economic skills aligned with Islamic values. This initiative aims to foster entrepreneurial spirit, enhance creativity, and promote student independence by utilizing local potential. The method involved technical skills training, production assistance, and both conventional and digital marketing training. The results indicated a significant increase in the students’ entrepreneurial knowledge and skills, the formation of student business groups, and the initial market recognition of their handicraft products. This program demonstrates that dayah has